Effect of teriparatide in fracture healing of intertrochanteric fracture: a prospective study - Singhal, Sanjeev K.; Aggarwal, Naresh; Sharma, Ajay (International Journal of Research in Orthopaedics, 2018)
Background: Intertrochanteric fracture is a relatively common and serious medical issue in geriatric trauma result in serious health problems and decrease health related quality of life. Faster time-to-union is important for early return to daily activities and reduction of complications. Teriparatide has been shown to accelerate fracture-healing. The purpose of the present prospective, randomized, controlled study was to evaluate the effect of teriparatide on the course of intertrochanteric fracture-healing. Methods: Forty patients of intertrochanteric fractures who underwent surgical intervention between June 2016 and May 2017 were enrolled in this prospective study and followed for minimum of six months. Group A included patients who received only calcium supplementation; patients in Group B received teriparatide along with calcium supplementation postoperatively. Results: The mean time to fracture healing was between 8-12 weeks for the treatment group, compared with 12-16 weeks for the control group. There was also significant effectiveness with regards to Parker and Palmer mobility score at 6 months. Conclusions: Postoperative use of teriparatide for 6 months appears to be an effective adjunct therapy in the treatment of patients with intertrochanteric fractures. However, because of the limited power of the study a large-scale cohort study is still required for determining the efficacy of teriparatide.